Method of placing flowable building material
By using recycled concrete aggregate in 3D concrete or mortar, the dependence problem on coagulant and thickener in the prior art is solved, and a lower cost and environmentally friendly 3D printing effect is achieved, while improving the printability and mechanical stability of the material.
Patent Information
- Application Number
- CN202380063867.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-07
- Filing Date
- 2023-09-07
- Publication Date
- 2025-04-11
AI Technical Summary
In existing 3D concrete or mortar printing technologies, building materials require the addition of coagulant and/or thickener to improve fluidity and mechanical stability, but this increases production complexity and cost, while also increasing environmental footprint.
Using flowable building materials containing recycled concrete aggregates, the reliable aggregates are reduced or eliminated by incorporating recycled aggregates into concrete or mortars, and the porous structure and high water absorption of recycled aggregates are used to improve the printability and mechanical stability of the material.
The use of thickeners and coagulants is achieved, reducing the cost and production complexity of 3D printing, while reducing the environmental footprint and improving the printability and mechanical stability of the material.
Smart Images

Figure BDA0005297804050000111 
Figure BDA0005297804050000121 
Figure BDA0005297804050000141
Abstract
Description
[0001] The invention relates to a method of placing a flowable building material comprising hydraulic cement and aggregates for layer-by-layer construction of structures and building components, for example for 3D concrete or mortar printing.
[0002] 3D printing is a construction technology, often referred to as "additive manufacturing", which consists in joining materials from 3D model data or other electronic data sources to produce an object layer by layer. Specifically, the successive layers of material are formed under computer control with the help of industrial robots. There have been proposals to develop 3D printers capable of producing structural building and infrastructure elements from building materials, which may be mortar or concrete. According to these proposals, the building material is extruded through a nozzle to build up the structural component layer by layer without the use of formwork or any subsequent vibration. The possibility of building structures without formwork is a major advantage in terms of production speed, building freedom, material saving and cost reduction.
[0003] Typically, 3D printing of building materials is a continuous process that includes delivering fresh concrete, mortar or micro-mortar to a deposition head and placing building materials through the outlet of the deposition head to form a concrete layer. While placing the concrete, mortar or micro-mortar, the deposition head moves under computer control to build up the building material layer according to the underlying 3D model. Specifically, the deposition head places strips of fresh concrete or mortar material. In order to allow the fresh concrete or mortar to move smoothly through each part of the delivery process to the deposition head, a consistent rheology of the fresh material must be guaranteed.
[0004] However, the building material must not only be fluid enough for conveying and extrusion purposes, but also strong enough to provide the mechanical stability required for 3D-printed structures before the hydraulic binder sets. Specifically, the lower layer of the building material should withstand the load applied by the upper layer without collapsing or deforming.
[0005] Therefore, flowable building materials suitable for 3D printing typically contain accelerators to reduce the initial setting time. However, binders with short initial setting times increase the risk of material accumulation in mixing devices, pumps and printing heads.
[0006] 3D-printed elements also require strong bonding strength between deposited layers to ensure sufficient overall strength of the 3D-printed structure. For this purpose, it is beneficial to lay down one layer while the previous one is still fresh. However, with hydraulic binders that have a short initial setting time, the operating flexibility is very limited.
[0007] From an operational flexibility point of view, it is desirable to have a flowable building material with a long initial setting time, i.e. a constant consistency that does not increase too much over time, as this would allow more time to adjust the printing process, e.g. changing printing parameters during the building process.
[0008] In order to accommodate some of the above requirements, it has been suggested to add thickeners and / or accelerators to flowable constructions in order to increase the yield stress of the newly placed material or to reduce its setting time. Starch ethers, cellulose ethers, water-soluble polyacrylamides, casein and / or welan gum have been suggested as rheology modifiers, and several accelerators have been tested, such as aluminum sulfate or sodium silicate.
[0009] However, the addition of additives, particularly accelerators and / or thickeners, complicates the production process and increases the cost of the building material. Therefore, the present invention is directed to an improved method of 3D concrete or mortar printing that reduces or eliminates the need to add accelerators and / or thickeners to the building material.
[0010] Another challenge in concrete technology is to reduce the environmental footprint of concrete and minimize the extraction of natural resources. Therefore, the present invention also aims to reduce the environmental footprint impact of 3D concrete or mortar printing.
[0011] To achieve these objectives, according to a first aspect, the present invention provides a method for placing a flowable building material comprising hydraulic cement and aggregate for layer-by-layer construction of structures and building components, such as for 3D concrete or mortar printing, the method comprising:
[0012] Delivering flowable building material to the deposition head,
[0013] while moving the deposition head, placing the building material through the outlet of the deposition head so as to form a layer of building material,
[0014] where successive layers of building materials are placed on top of each other,
[0015] The aggregate comprises recycled concrete aggregate.
[0016] The present invention is therefore based on the idea of at least partially replacing aggregates of natural origin with recycled concrete aggregates.
[0017] The term aggregate as used herein encompasses sand, crushed stone and coarse aggregate.
[0018] Recycled concrete aggregates have high water absorption due to their porous structure and often also include reactive clinker particles from the cement paste in which they are encapsulated. These often have a negative impact on the fresh properties of concrete, including reduced slump over time and more rapid slump loss. These are considered to be negative impacts for applications where fresh concrete flow is important.
[0019] However, it has been found that this negative effect is beneficial for 3D printing of concrete, as 3D printing with recycled aggregates in concrete leads to reduced slump and rapid slump loss. This translates into improved printability and buildability.
[0020] By incorporating recycled aggregates in concrete or mortar for 3D printing, the following benefits have been observed:
[0021] - Reduce or eliminate the need to use thickeners and / or accelerators. This reduces the cost of 3D printed concrete and simplifies the production process,
[0022] - The environmental footprint of 3D printed concrete is reduced by incorporating waste materials instead of aggregates extracted from quarries.
[0023] Recycled concrete aggregates are produced from concrete demolition waste by crushing the waste material, separating foreign materials such as steel bars, and dividing the crushed material into various fractions with the desired particle size. Recycled concrete aggregates can be characterized by their composition or other properties, as defined in European Standard EN 933-11:2009.
[0024] In a preferred embodiment, the recycled aggregate or crushed stone of the present invention is preferably characterized by the following parameters:
[0025] Rc+Ru: 70%-100%, preferably 90%-100%,
[0026] X+Rg: 0%-2%, preferably 0–1%,
[0027] Ra: 0%-10%, preferably 0–1%,
[0028] Rb: 0%-10%, preferably 0–1%,
[0029] FL: 0%-2%,
[0030] wherein Ru (unbound stone), Ra, Rb, X, Rg, Rc (crushed concrete) and FL are as defined in EN 933-11:2009, and wherein the percentages are expressed as percentages by weight of the total amount of recycled aggregate.
[0031] The replacement rate of recycled aggregate to naturally occurring concrete aggregate can preferably be 10% to 50% by weight of the total weight of aggregate used in the building material. Preferably, the replacement rate of recycled aggregate to naturally occurring concrete aggregate is selected to be 10-20% by weight, 10-30% by weight, or 10-40% by weight of the total weight of aggregate used in the building material.
[0032] Alternatively, the replacement rate can also be selected in the range of 3.5-10 wt. %, preferably 3.5-6 wt. %. It has been found that such low amounts of recycled aggregate are sufficient to at least partially replace the role of the thickener in the building material composition. At the same time, such low amounts limit the quality changes that are inevitably caused by the addition of recycled aggregate.
[0033] The amount of recycled concrete aggregate present in the building material is preferably selected so that the layer of material placed has sufficient stability not to collapse under its own weight or the weight of a subsequent layer placed on top. In this respect, a preferred mode of operation is that after the placement of a first layer of building material, at least one subsequent layer of building material is placed onto the first layer, wherein the amount of recycled concrete aggregate is selected so that a yield stress is reached so that the first layer does not collapse under the load of the at least one subsequent layer.
[0034] In this context, "no collapse" means that the height of the layer does not decrease by more than 10%, preferably by more than 5%, under the load of at least one subsequent layer.
[0035] According to a preferred mode of operation, the first layer of building material is allowed to rest during a period not exceeding 2 minutes, preferably during a period of 30-60 seconds, before a subsequent layer of building material is placed onto said first layer of building material.
[0036] According to a preferred embodiment of the invention, the yield stress of the newly placed building material measured 30 seconds after its placement is 300-3000 Pa. Therefore, it is preferred to select the amount of recycled concrete aggregate present in the building material so as to provide a yield stress of 300-3000 Pa. The yield stress is measured with a scissometer. The scissometer comprises a blade which is inserted into the material to be measured and applies increasing torque to it. When damage occurs in the material, the blade starts to rotate, usually when the torque reaches its maximum value, which is considered to be a characteristic value representing the yield stress of the material. The yield stress measurement is preferably carried out within 30-60 seconds after the material has been placed.
[0037] Aggregates used in building materials based on hydraulic binders can be in the form of natural sand and / or natural crushed stone. Sand is usually defined as aggregate with a particle size of 0-4 mm and crushed stone as aggregate with a particle size of 4-10 mm. Aggregates can have a particle size of up to 20 mm or 32 mm. The particle size of aggregates is measured by sieving.
[0038] With the present invention, natural sand or natural crushed stone or both can be at least partially replaced by respective fractions of recycled concrete aggregate.Aggregates between 10 mm and 20 mm can also be partially replaced by respective fractions of recycled concrete aggregate.
[0039] According to a preferred embodiment of the present invention, the recycled concrete aggregate comprises a fine fraction with a particle size <4 mm and / or a coarse fraction with a particle size of 4-20 mm, preferably 4-10 mm, measured by sieving.
[0040] Preferably, the aggregate comprises a fine fraction with a particle size of <4 mm and 3.5-10 wt. %, preferably 3.5-6 wt. %, of the fine fraction consists of recycled concrete aggregate.
[0041] As previously mentioned, the benefits of using recycled concrete aggregates are at least partly due to their porous structure. The porosity of recycled concrete aggregates can be characterized, for example, by their water absorption and / or their density.
[0042] According to a preferred embodiment, the recycled concrete aggregate may have a water absorption of 5-20%, preferably 10-20%, measured according to NF EN 1097-6, 2022.
[0043] According to a preferred embodiment, the recycled concrete aggregate may have a mass of 1.7-2.7 kg / dm 3 of particle density.
[0044] Recycled concrete aggregates may preferably have a packing density of 0.48-0.65 as measured by NF EN 1097-3 issued in 1998. Such a loose packing density allows for a reasonable paste volume, i.e., a reasonable amount of binder and additives. This is beneficial to reducing the environmental impact of mortar / concrete and reducing costs.
[0045] As mentioned previously, the present invention allows minimizing or even eliminating the use of thickeners. Thus, in a preferred embodiment, the concrete or mortar used in the present invention allows reducing the amount of thickeners and / or accelerators by 50% by weight compared to the same concrete or mortar containing only aggregates extracted from a quarry. In an even more preferred embodiment, the building material does not contain any thickeners and / or accelerators.
[0046] It is understood that as used herein, thickener refers to a viscosity-modifying admixture as defined in European Standard EN-934-2 of August 2012, which restricts segregation in fresh concrete or mortar by increasing cohesion, i.e., the separation of concrete components according to their respective density and weight. Examples of thickeners include suspensions of starch ethers, cellulose ethers, water-soluble polyacrylamides, caseins, suspensions of colloidal silica or liquid alkali-swollen emulsions of polymers (ASE, HASE) and / or welan gum.
[0047] As also mentioned above, the present invention allows minimizing or even eliminating the use of accelerators. Therefore, a preferred embodiment is provided in which the building material does not contain any accelerators.
[0048] Alternatively, the setting accelerator may be added to or present in the building material.According to a preferred embodiment, the setting accelerator is added to the building material in the deposition head, ie after the step of conveying the flowable building material to the deposition head and before the step of placing the building material through the outlet of the deposition head.
[0049] It will be understood that accelerators refer to a group of accelerating admixtures or hardening accelerators defined in European Standard EN-934-2 of August 2012. Examples of accelerators include calcium nitrate, calcium nitrite, calcium formate, calcium chloride, aluminum salts, sodium silicate and thiocyanates.
[0050] The building material may be a cement mortar or cement micromortar, ie a mixture of hydraulic cement, potentially further mineral components (such as ground limestone), water, sand and chemical admixtures.
[0051] The building material may also be concrete, ie a mixture of hydraulic cement, potentially further mineral components (such as ground limestone), water, sand, crushed stone and chemical admixtures.
[0052] In a preferred embodiment, the building material is a flowable ultra high performance concrete, i.e. a mixture of cement, fine limestone material, fine sand and / or sand, a high range water reducing admixture, a latent accelerating admixture and water, which exhibits a compressive strength of at least 100 MPa at 28 days.
[0053] Preferably the step of placing the building material comprises extruding the building material in slurry form through a nozzle of a deposition head.
[0054] The conveying step of the method of the present invention comprises conveying the building material in a flowable state to the deposition head. In particular, the conveying of the building material is carried out by pumping. Preferably, the material is conveyed in a wet state and is ready to be placed without the need to add any additional components.
[0055] Fresh building material, such as fresh concrete or fresh mortar, is preferably stored in a silo or any other storage container or mixer in a pre-mix delivery vehicle and is delivered from the storage location directly to the deposition head.
[0056] In order to achieve the above-mentioned conveyability or pumpability, a water reducing agent, in particular a plasticizer or superplasticizer, preferably a plasticizer based on polyoxypolycarboxylate or phosphonate, is preferably added to or present in the building material before the conveying step. Preferably, the flowable building material contains both a phosphonate-based superplasticizer and a polycarboxylate-based superplasticizer.
[0057] Water reducers make it possible to reduce the amount of mixing water for a given processability by typically 10-15%. As examples of water reducers, mention may be made of lignin sulfonates, hydroxycarboxylic acids, carbohydrates and other specific organic compounds, such as glycerol, polyvinyl alcohol, sodium alumino-methyl-siliconate and p-aminobenzenesulfonic acid, as described in Concrete Admixtures Handbook, Properties Science and Technology, VS Ramachandran, Noyes Publications, 1984.
[0058] Superplasticizers belong to a new class of water reducers, capable of reducing the water content of the mixed water by about 30% by mass at a given processability. As examples of superplasticizers, PCP superplasticizers may be mentioned. According to the invention, the term "PCP" or "polyoxypolycarboxylate" is to be understood as a copolymer of acrylic acid or methacrylic acid and its esters of polyoxyethylene (POE).
[0059] Preferably, the building material comprises 0.4-1 wt. %, more preferably 0.45-0.75 wt. %, based on the total weight of the hydraulic cement, of one or more water reducers, plasticizers or superplasticizers. If more than one type of water reducer, plasticizer or superplasticizer is used, the amount of 0.4-1 wt. %, preferably 0.45-0.75 wt. %, refers to the total amount of all such ingredients based on the total weight of the hydraulic cement.
[0060] Flowable building materials include hydraulic cement, which is a hydraulic binder including at least 50% by weight of CaO and SiO2, which solidifies due to the chemical hydration reaction between dry ingredients and water. In addition to CaO and SiO2, hydraulic cement may also include other components. Various mineral additives, such as silica fume, granulated blast furnace slag (GBFS), fly ash, natural pozzolan, calcined clay, ground limestone or concrete demolition waste, may be added to portland cement to obtain portland composite cement. Mineral additives, usually between 10 and 50% by weight of the hydraulic cement gross weight, are ground granulated blast furnace slag, fly ash, pozzolan, ground limestone or its mixture in most applications. Adding silica fume may be particularly useful for producing high-strength 3D printing mortar or concrete, that is, at least 70Mpa in 28 days of compressive strength.
[0061] Preferably, hydraulic cement consists of Portland cement clinker mixed with any one or several of the main and minor ingredients described in cement standard EN 197-1 of April 2012 and calcium sulphate. Hydraulic cement may also include ground particles of concrete demolition waste, or ground slag not produced from a blast furnace.
[0062] Preferably the hydraulic cement comprises at least 30% by weight Portland cement clinker.
[0063] Preferably the hydraulic cement comprises at least 10% by weight of a supplementary binding material, preferably ground granulated blast furnace slag.
[0064] Suitable cements are those described in the European standard NF EN 197-1 of April 2012, or mixtures thereof, preferably cements of the CEM I, CEM II, CEM III, CEM IV or CEM V type.
[0065] The hydraulic cement may also be fine or ultrafine cement, ie, a hydraulic cement ground to a finer fineness than standard hydraulic cement. The fineness may be, for example, greater than 5000 cm 2 / g, and reaches up to 13000cm 2 / g or even 15000cm 2 / g value (expressed as cement Brinell fineness).
[0066] According to a preferred embodiment, the flowable building material does not contain any aluminate cement, such as calcium aluminate cement. Alternatively, aluminate cement, such as calcium aluminate cement or calcium sulfoaluminate cement, may be present in an amount of <5 wt%, preferably <2.0 wt%, based on the total amount of hydraulic cement.
[0067] According to a preferred embodiment, the hydraulic cement comprises Portland cement and aluminate cement, wherein the aluminate cement is present in an amount of <5% by weight, preferably <2% by weight, based on the total amount of hydraulic cement.
[0068] Calcium aluminate cement is a cement consisting mainly of hydraulic calcium aluminate. Alternative names in French are "aluminous cement", "high-alumina cement" and "aluminous cement". Calcium aluminate cements have a short initial setting time, so they are considered less preferred. Hydraulic cements with a short initial setting time increase the risk of material accumulation in the deposition head. In addition, a short initial setting time may reduce the bond strength between layers placed on top of one another, because when the subsequent layer is placed, the previous layer may no longer be fresh. Limiting the content of calcium aluminate cement is also preferred in terms of cost, because calcium aluminate cement is relatively expensive.
[0069] In addition, the flowable building material may contain a mineral filler, such as limestone. Adding a fine fraction of the mineral filler may be particularly beneficial for producing high-strength 3d-printed mortar or concrete. Preferably, the mineral filler, such as limestone, has a particle size of <50 μm, preferably <40 μm. More preferably, the mineral filler, such as limestone, comprises a fine fraction having a particle size distribution characterized by a D50 of 3-5 μm and a D90 of 8-12 μm and a coarse fraction having a particle size distribution characterized by a D50 of 10-12 μm and a D90 of 35-40 μm.
[0070] Additionally, the aggregate present in the flowable building material may comprise fine sand having a particle size <1 mm, a secondary sand having a particle size of 1-4 mm and optionally coarse aggregate (>4 mm and <32 mm).
[0071] The flowable building material may comprise metal fibers and / or organic fibers and / or glass fibers. The amount of fibers by volume is generally 0.5 to 8% relative to the total volume of the fresh concrete composition. The amount of metal fibers, expressed by volume of the final hardened concrete, is generally less than 3%, for example 0.5 to 2.5%, preferably about 2%. The amount of organic fibers, expressed on the same basis, is generally 1 to 8%, preferably 2 to 5%. The metal fibers are generally selected from steel fibers, for example high-strength steel fibers, amorphous steel fibers or stainless steel fibers. The steel fibers may optionally be coated with a non-ferrous metal, such as copper, zinc, nickel (or their alloys).
[0072] The individual length (l) of the metal fibers is generally at least 2 mm and preferably 10 to 30 mm. The ratio l / d (d being the diameter of the fiber) is generally 10 to 300, preferably 30 to 300, preferably 30 to 100.
[0073] Organic fibers include polyvinyl alcohol (PVA) fibers, polyacrylonitrile (PAN) fibers, polyethylene (PE) fibers, high density polyethylene (HDPE) fibers, polypropylene (PP) fibers, homopolymer or copolymer fibers, polyamide or polyimide fibers. Mixtures of these fibers can be used. The organic reinforcing fibers used in the present invention can be classified as follows: high modulus reactive fibers, low modulus non-reactive fibers and low modulus reactive fibers. The presence of organic fibers makes it possible to change the behavior of concrete in relation to heat or fire.
[0074] The individual length of the organic fibers is preferably 5 to 40 mm, preferably 6 to 12 mm. The organic fibers are preferably PVA fibers.
[0075] A side effect of adding recycled concrete aggregates to building materials can be a reduction in the compressive strength of concrete. However, this can be solved by correcting the amount of mixing water in the concrete mix: it is indeed found that recycled concrete aggregates are usually not dried, and water is added to the concrete composition. Proper correction for this corrects the water-cement ratio in the concrete composition, which solves the problem of strength loss.
[0076] The effective water / cement ratio (weight / weight ratio) of the building material used in the present invention is preferably 0.4 to 0.6, more preferably 0.40 to 0.45. The water / binder ratio is defined as the mass ratio of the amount of water to the dry mass of hydraulic cement (Portland cement and mineral additives).
[0077] According to a second aspect, the present invention relates to the use of a building material comprising hydraulic cement and aggregate for building structures and building components layer by layer, for example for 3D concrete or mortar printing, which comprises placing the building material through the outlet of the deposition head while moving the deposition head so as to form layers of building material, wherein consecutive layers of building material are placed on top of each other, wherein the aggregate comprises recycled concrete aggregate.
[0078] The invention is now explained with respect to the following examples of building material compositions tested for 3D printing applications.
[0079] The concrete composition is shown in Table 1, where the following materials were used:
[0080] Cement: CEM I 52.5R from Le Teil
[0081] Limestone filler: Omyacarb, provided by Omya
[0082] Thickener: Mecellose Hiend 2001, provided by Lotte Fine Chemical
[0083] Extrusion aid: Cimsil A-55, provided by Tolsa SA
[0084] SP1 (superplasticizer): Optima 100, provided by Chryso
[0085] SP2 (superplasticizer): MasterPol.300, provided by MBCC
[0086] Sand 1: Petite-craz 0 / 1
[0087] Sand 2: Petite-craz 1 / 5
[0088] Gravel: Petite-craz 5 / 10
[0089] RC sand 1: Recycled concrete sand 0 / 4, with the following characteristics:
[0090] oTrue density (kg / l): 1.86
[0091] oWet density (kg / l): 2.17
[0092] oAbsolute density (kg / l): 2.69
[0093] oWater absorption (%): 16.63
[0094] oBulk density (kg / l): 1.072
[0095] oCompacity: 0.576
[0096] oPorosity: 0.424
[0097] RC sand 2: Recycled concrete sand 0 / 2, with the following characteristics:
[0098] oTrue density (kg / l): 2.11
[0099] oWet density (kg / l): 2.32
[0100] oAbsolute density (kg / l): 2.68
[0101] oWater absorption (%): 10.03
[0102] oBulk density (kg / l): 1.072
[0103] oFilling degree: 0.613
[0104] oPorosity: 0.387
[0105] RC crushed stone: Recycled concrete crushed stone 4 / 10, with the following characteristics:
[0106] oTrue density (kg / l): 2.24
[0107] oWet density (kg / l): 2.39
[0108] oAbsolute density (kg / l): 2.65
[0109] oWater absorption (%): 6.94
[0110] oBulk density (kg / l): 1.240
[0111] oFilling degree: 0.554
[0112] oPorosity: 0.446
[0113] Fiber: Neuflex 6mm, provided by NEUVENDIS SPA
[0114]
[0115]
[0116] The reference composition is a concrete suitable for 3D printing, the concrete comprising aggregates with a Dmax of 10 mm and not comprising any recycled concrete aggregate. In order to improve printability and in order to achieve a sufficient yield strength immediately after placing a layer of concrete, the concrete composition comprises a thickener.
[0117] Concrete compositions A-1, A-2, A-3, A-4, B-1, B-2, C, D and E contain recycled concrete aggregates and are therefore considered to correspond to embodiments of the present invention. They demonstrate the benefits of incorporating recycled concrete aggregates into concrete for 3D printing, i.e., reducing or eliminating thickeners.
[0118] In contrast, concrete compositions Am and Bm comprise the same amount of thickener as the reference composition and are therefore less suitable as their yield strengths tend to be higher than that which is optimal for printable concrete.
[0119] The table above shows the results of 3D printing tests conducted with concrete compositions regarding yield strength, buildability and 7-day compressive strength. The yield stress is measured using a shear accumulator. The shear accumulator consists of a blade that is inserted into the material to be tested and applies increasing torque to it. When failure occurs in the material, the blade begins to rotate, usually when the torque reaches its maximum value, which is considered to be a characteristic value representing the yield stress of the material.
[0120] The 7-day compressive strength was measured according to EN 196-1:2016. The buildability was tested according to the method described in the following article: C. Zhang, Z. Hou, C. Chen, Y. Zhang, V. Mechtcherine, Z. Sun, Design of 3D printable concrete based on the relationship between flowability of cement paste and optimal aggregate content, Cem. Concr. Compos. 104 (2019) 103406, https: / / doi.org / 10.1016 / j.cemconcomp.2019.103406.
[0121] Comparing Mix A-1 with Am (or Mix B-1 with Mix Bm), it can be seen that the recycled concrete aggregate has a similar effect as the thickener in increasing the yield strength of the placed building material. This suggests that the use of recycled concrete aggregate can replace the thickener.
[0122] Mix A-2 is an improved mix whose compressive strength is increased by reducing the mixing water (the reduction in water corresponds to approximately the amount of water absorbed by the recycled concrete aggregate).
[0123] Mixture A-3 is similar to A-2 except that a different superplasticizer is used.
[0124] Mixture A-4, when compared to mixture A-1, has a reduced amount of superplasticizer, but additionally comprises a thickener.
[0125] Mix B-1, compared to Mix A-1, has an increased amount of recycled concrete aggregate.
[0126] With Mix B-2, the only change compared to Mix B-1 was the reduction in the amount of superplasticizer. This suggests that the yield strength can be further improved, especially 30 minutes after mixing. In other words, the use of superplasticizer can reduce the yield strength development, especially from 30 minutes after mixing and beyond.
[0127] Mix C, compared to Mix A-1 and Mix B-1, has a further increased amount of recycled concrete aggregate.
[0128] With Mix D, the only difference compared to Mix A-1 was that the reclaimed sand came from another supplier.
[0129] Mix E has the highest amount of recycled aggregate, and not only recycled sand but also recycled crushed stone is incorporated into the mix.
[0130] The above concrete composition does not require any admixture to be added in the deposition head.
[0131] The present invention can also be implemented with a two-component concrete system, wherein the building material is delivered to a deposition head, an admixture is added to and mixed into the building material, and the resulting final mixture is placed through an outlet of the deposition head. Preferably, the admixture is a setting accelerator. The following examples illustrate embodiments of a two-component concrete system for 3D printing.
[0132] Component A (concrete mix), component B (Floquat ASL, supplied by SNF Floerger, based on aluminum sulfate) and the properties are shown in the table below:
[0133]
[0134]
[0135] The table above gives information for two two-component mixtures: a reference without demolition sand and a mixture with demolition sand. The mixture with demolition sand has a lower water content, which explains the higher demand for Optima 100, but more importantly, it has a significantly higher yield stress using a slightly lower dosage of component B.
[0136] The dry mortar contained 81.4% by weight of hydraulic binder (Holcim Susteno produced in Switzerland, comprising ground concrete demolition waste) and 18.5% by weight of limestone filler.
[0137] Demolition sand is characterized by the following parameters:
[0138]
[0139] The particle size of sand is measured by sieving.
[0140] A further concrete composition according to a preferred embodiment of the present invention comprises the components listed in the following table.
[0141]
[0142]
[0143] <![CDATA[Kg / m 3 ]]> Cement (CEMIIIPARM ALTKIRCH) 749 Fine limestone filler (D50~2.5μm) 165 Demolition Sand 41 PCE type superplasticizer (powder) 0.91 Liquid superplasticizer, pumping aid 6.69 Sodium aluminate 11.14 Effective water 278.98 natural sand 994
Claims
1. A method of placing a flowable building material comprising hydraulic cement and aggregate for layer-by-layer construction of structures and building components, such as for 3D concrete or mortar printing, the method comprising: Delivering flowable building material to the deposition head, placing building material through an outlet of the deposition head while moving the deposition head so as to form a layer of building material, where successive layers of building materials are placed on top of each other, The aggregate comprises recycled concrete aggregate.
2. The method according to claim 1, wherein 10-50 wt. % of the aggregate consists of recycled concrete aggregate.
3. The method according to claim 1, wherein 3.5-10 wt. %, preferably 3.5-6 wt. %, of the aggregate consists of recycled concrete aggregate.
4. The method according to claim 1, 2 or 3, wherein the recycled concrete aggregate comprises a fine fraction having a particle size <4 mm and / or a coarse fraction having a particle size of 4-20 mm.
5. The method according to any one of claims 1 to 4, wherein the aggregate comprises a fine fraction with a particle size < 4 mm, and wherein 3.5-10 wt.-%, preferably 3.5-6 wt.-%, of the fine fraction consists of recycled concrete aggregate.
6. The method according to any one of claims 1 to 5, wherein the recycled concrete aggregate has a water absorption measured according to NF EN 1097-6, 2022, of 5-25%, preferably 10-20%.
7. The method according to any one of claims 1 to 6, wherein the recycled concrete aggregate has a mass of 2.5-2.7 kg / dm 3 The absolute density of .
8. The method according to any one of claims 1 to 7, wherein the recycled concrete aggregate has a loose packing density of 0.48-0.65 measured according to EN 1097-3 issued in 1998.
9. A method according to any one of claims 1 to 8, wherein the step of placing the building material comprises extruding the building material in slurry form through a nozzle of a deposition head.
10. The method according to claim 1, wherein after placing a first layer of building material, at least one subsequent layer of building material is placed onto the first layer, wherein the yield stress of the building material is adjusted so that the first layer does not collapse under the load of the at least one subsequent layer.
11. A method according to any one of claims 1 to 10, wherein the freshly placed building material has a yield stress of 300 - 3000 Pa measured 30 seconds after its placement.
12. The method according to any one of claims 1 to 11, wherein the hydraulic cement comprises at least 30% by weight of Portland clinker.
13. A method according to any one of claims 1 to 12, wherein the hydraulic cement comprises at least 10% by weight of a supplementary binding material, preferably ground granulated blast furnace slag.
14. The method according to claim 1, wherein a water reducing agent, in particular a plasticizer or a superplasticizer, preferably a plasticizer based on polyoxypolycarboxylates or phosphonates, is added to or is present in the building material before the conveying step, wherein conveying the building material is carried out by pumping.
15. A method according to any one of claims 1 to 14, wherein the admixture, preferably the setting accelerator and / or the thickener, is added to the building material in the deposition head, i.e. after the step of conveying the flowable building material to the deposition head and before the step of placing the building material through the outlet of the deposition head.
16. Use of a building material comprising hydraulic cement and aggregate for building structures and building components layer by layer, for example for 3D concrete or mortar printing, comprising placing the building material through an outlet of a deposition head while moving the deposition head so as to form layers of building material, wherein successive layers of building material are placed on top of each other, wherein the aggregate comprises recycled concrete aggregate.